2021
DOI: 10.1111/ijmr.12272
|View full text |Cite
|
Sign up to set email alerts
|

Connecting content and structure: A review of mechanisms in entrepreneurs’ social networks

Abstract: Network studies in the entrepreneurship domain suffer from an incomplete theorization of how the content of social capital relates to network relationships and structures in which entrepreneurs are embedded or embed themselves. This study presents a systematic review of the various ways in which the interaction between content (e.g. cognition and resources) and social structure has been studied within entrepreneurship. Based on this review, we develop a more integrative account of the underlying action mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 159 publications
(252 reference statements)
1
26
0
4
Order By: Relevance
“…In addition, this research distinguishes the effects of network size and strength on BMI, which is rare and called for research (Partanen et al, 2020). Prior research presents inconsistent findings on the specific network dimensions that influence innovation (Burg et al, 2021; Partanen et al, 2020). For example, some studies determined that network size positively impacted innovation (Hansen et al, 2005; Raz & Gloor, 2007), whereas other studies showed no consistent results (Lechner et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, this research distinguishes the effects of network size and strength on BMI, which is rare and called for research (Partanen et al, 2020). Prior research presents inconsistent findings on the specific network dimensions that influence innovation (Burg et al, 2021; Partanen et al, 2020). For example, some studies determined that network size positively impacted innovation (Hansen et al, 2005; Raz & Gloor, 2007), whereas other studies showed no consistent results (Lechner et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…A general view is that firm positioning with network structures has a significant effect on resource flows and, thus, on entrepreneurial outcomes (Hoang & Yi, 2015). It is proposed that two network structure characteristics, network size and network strength, are particularly important for determining BMI (Burg et al, 2021;Hoang & Yi, 2015;Hoanga & Antoncich, 2003;Sullivan & Ford, 2014).…”
Section: Entrepreneurial Network and Bmimentioning
confidence: 99%
See 3 more Smart Citations